Pemikiran Ulama Nusantara Tentang Penguatan Pemikiran Nilai-Nilai Islam Rahmatan Lil‘Alamin Yang Berkemajuan - Baihaqi, Muhammad Ryja; Hendriyanti, Devita; Sadiyah, Girllis Nurrukhyati Ramdanis; Fadhil, Abdul (CV Insan Kreasi Media, 2025)
This article examines the intellectual contributions of Nusantara scholars in strengthening the values of Islam rahmatan lil ‘alamin that are progressive, serving as a response to social and cultural dynamics alongside the challenges of modernity, by highlighting how Nusantara scholars have formulated a moderate, inclusive concept of Islam oriented toward universal welfare through the integration of religious texts, local traditions, and global contexts. The research methodology employed encompasses comprehensive literature review and critical analysis of classical and contemporary works by prominent Nusantara scholars, including KH. Hasyim Asy'ari, KH. Ahmad Dahlan, Buya Hamka, and other influential figures who pioneered progressive Islamic thought in the archipelago, with an analytical framework that integrates historical contextualization, theological interpretation, and socio-cultural examination to understand the evolution of moderate Islamic discourse in Nusantara. Through systematic documentation of scholarly methodologies such as al-mu'āmalāt bi al-'urf, al-maqāṣid al-syarī'ah, al-qiyās al-mutassil, and al-ijtihād al-inklusif- integratif, this study reveals the sophisticated intellectual mechanisms employed by Nusantara scholars in responding to contemporary challenges while maintaining doctrinal authenticity. This research identifies strategic approaches for strengthening these values in contemporary society through humanistic education, cultural engagement, institutional reinforcement, and digital literacy, thereby affirming that Nusantara scholars' intellectual legacy provides a viable framework for addressing global civilizational challenges through a paradigm of Islam that is simultaneously authentic, progressive, and universally beneficial.